Antarctic plant rbcL and ITS2 sequencing for determination of possibility in DNA barcoding - Duplij, V.; Matvieieva, N.; Shakchovsky, A.; Kishchenko, O.; Kurbatova, L. (Ukrainian Antarctic Journal, 2012)
The extraction technique of total DNA of Antarctic plants cultivated in vitro was optimized. The possibility of application of used in DNA barcoding primers for amplification of chloroplast and nuclear DNA (trnH-psbA, rbcL, ITS2, ITS) of Antarctic plants such as Decshampsia antarctica E. Desv., Colobanthus quitensis (Kunth) Bartl., Warnstorfia fontinaliopsis (Müll.Hal.) Ochyra, Bryum pseudotriquetrum (Hedw.) G. Gaertn., B. Mey. & Scherb., Bryum archangelicum Bruch & Schimp. (2 samples), Pohlia nutans (Hedw.) Lindb. was investigated. It was shown that primers for rbcL gene and intergenic spacer ITS2 can be used in DNA barcoding both Vascular plants and Bryophyta of Antarctica. After the sequence analysis of rbcL and ITS2 one sample has been determined to within a species, and three samples to within a genus.